STUDY OF AGE THRESHOLD OF TRAUMATIC MEMORY - Azarian, A. (Արդի հոգեբանություն, 2022)
The article is devoted to the study of age threshold of traumatic memory. The study of memories of young children is started conducted in Children’s Psychotherapy Center in Kirovakan (Vanadzor) who experienced the devastating Armenian earthquake in 1988 using the data collected during evaluations of the affected children. The research has shown that the versatility of behavioral memory operates according to different rules than verbal one; it does not require verbal skills and conscious awareness and therefore, does not depend on the children’s age.